THE OLD WORLD SPECIES OF LUDWIGIA (INCLUDING HISSIAEA), WITH A SYNOPSIS OF THE GENUS (ONAGRACEAE) - Peter H. Raven (BRIN Publishing (Penerbit BRIN), 1963)
Evidence is presented in support of t he reduction of Jussiaea and Oocarpon to rigid. This combined genus then consists of 75 species,distributed among 17 .lions, of which Africana, Caryopkylloidea,Brenania, Seminuda, Cryptosperma, tyonia, and Miquelia are proposed in this paper, and Prieuria, N em atopy xis, Fis-docarpa, and Oocarpon are used for the first time as sections of J-udwigia. The ribution of species with pollen falling in tetrads has been compared with those rtich the grains fall singly. Of the 16 sections for which this character is known, have the pollen falling- in tetrads, five have it falling singly, and two (Micro-wm and Dantia) have both types of pollen in different species. A revision of the 23 ties of Lurhvigia in the Old World is presented, with complete synonymy; 13 hese species arc restricted to the Old World. New combinations are L. inclino.t